Football player ranking generated by multivariate methods (Research, Society and Development, 2022)
The objective was to build a ranking of football players based on multivariate methods. The players evaluated were the winners of FIFA; UEFA; Ballon D'Or; FIFPro; World Soccer; Golden Ball World Cup and King of América awards. A total of 95 players were evaluated based on the variables: games played, wins, draws, losses, goals scored, yellow/red cards, awards, dream team, title in national leagues/ continental championships in a football club, title in world cups/ continental championship in a national team, Olympics gold medal. We performed the multivariate clustering and principal components analyses. The grouping technique resulted in three groups: regionally renowned players (Group 1), renowned players for their extraordinary performance (Group 2), and globally renowned players (Group 3). The players in Group 2, except for Maradona, reached the highest indexes. The leaders of the ranking were Messi, Cristiano Ronaldo, Xavi, Pelé, and Iniesta.